1990
DOI: 10.1016/0885-5765(90)90079-d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various stress responses in oat in compatible and nonhost resistant interactions with rust fungi

Abstract: The role of extracellular fl-1,3-glucanases and chitinases was investigated in oat leaves after infection with different rust fungi . The oat leaves (Avena sativa L .) were inoculated with the compatible rust Puccinia coronata f. sp . avenae and the two nonpathogens Puccinia recondita f. sp . tritici and Puccinia graminis f. sp. tritici . No alterations in enzyme activities were found in the compatible interaction . In the nonhost interaction with P. recondita ff sp . tritici (1-1,3-glucanase and chitinase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…Our observation that Al toxicity induces a l,3-|3-glucanase is consistent with previous reports that these enzymes are induced by other metal ions including Co, Ba, Mn, Hg, and Ag (Fink et al, 1990). Generally, l,3-/3-glucanases play an important role in defense against fungal attack in both dicotyledonous and monocotyledonous plants (Simmons, 1994); however, their role in metal toxicity is not known.…”
Section: Discussionsupporting
confidence: 81%
“…Our observation that Al toxicity induces a l,3-|3-glucanase is consistent with previous reports that these enzymes are induced by other metal ions including Co, Ba, Mn, Hg, and Ag (Fink et al, 1990). Generally, l,3-/3-glucanases play an important role in defense against fungal attack in both dicotyledonous and monocotyledonous plants (Simmons, 1994); however, their role in metal toxicity is not known.…”
Section: Discussionsupporting
confidence: 81%
“…According to an earlier hypothesis (Goodman and Novacky 1994;Agrios 1997), incompatible pathogens must induce the HR phenotype in a nonhost plant. However, more recent data have shown that even pathogenic bacteria, which cause severe symptoms on a host plant, will not induce HR on a nonhost plant (Fink et al 1990;Jakobek and Lindgren 1993;Kamoun et al 1998;Klement et al 1999). These results indicated a requirement for a new model to explain Type I nonhost resistance.…”
Section: Resultsmentioning
confidence: 88%
“…avenae) in incom patible com binations (M ayam a et al, 1982; M ayam a et al, 1981). The induction of avenanthram ides can be reproduced by tre atm e n t w ith elicitors such as Nacetylchitooligosaccharides (B ordin et al, 1991), victorin C (M ayam a et al, 1986), heavy m etal ions (Fink et al, 1990), and the calcium ionophore A23187 . In addition, the oc currence of avenanthram ides in oat grains and hulls as constitutive com ponents has been found (Collins, 1986;Collins, 1989;Collins et a l, 1991).…”
Section: Discussionmentioning
confidence: 99%